2000
DOI: 10.1097/00008571-200012000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of phenol sulfotransferase activity (SULT1A1) genotype to sulfotransferase phenotype in platelet cytosol

Abstract: Sulfation catalysed by human cytosolic sulfotransferases is generally considered to be a detoxification mechanism. Recently, it has been demonstrated that sulfation of heterocyclic aromatic amines by human phenol sulfotransferase (SULT1A1) can result in a DNA binding species. Therefore, sulfation capacity has the potential to influence chemical carcinogenesis in humans. To date, one genetic polymorphism (Arg213His) has been identified that is associated with reduced platelet sulfotransferase activity. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
81
0
1

Year Published

2003
2003
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(86 citation statements)
references
References 48 publications
4
81
0
1
Order By: Relevance
“…Therefore, people with the rapid sulfonylation alleles would be less susceptible to BPA toxicity and would have higher levels of conjugated BPA in urine. As the SULT1A1*1 allele is known to be rapid sulfonylation allele (Raftogianis et al 1997;Nowell et al 2000), its presence is suspected to assist rapid disposal of environmental BPA sources. However, urinary BPA levels were not significantly different between SULT1A1*1/*1 subjects and SULT1A1*1/*2 subjects in our study (Table 4).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, people with the rapid sulfonylation alleles would be less susceptible to BPA toxicity and would have higher levels of conjugated BPA in urine. As the SULT1A1*1 allele is known to be rapid sulfonylation allele (Raftogianis et al 1997;Nowell et al 2000), its presence is suspected to assist rapid disposal of environmental BPA sources. However, urinary BPA levels were not significantly different between SULT1A1*1/*1 subjects and SULT1A1*1/*2 subjects in our study (Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…Among phase II enzymes, sulfotransferases (SULTs) and uridine diphosphate glucuronosyltransferases (UGTs) are known to be involved in BPA metabolism (Elsby et al 2001;Yokota et al 1999;Suiko et al 2000;Raftogianis et al 1997). Among SULTs, SULT1A1 is thought to sulfate phenolic compounds like BPA, and is considered to be genetically polymorphic (Raftogianis et al 1997;Nowell et al 2000;Carlini et al 2001) in human. There are four known different alleles in SULT1A1, and are reported as: SULT1A1*1, SULT1A1*2, SULT1A1*3, and SULT1A1*4 in the literature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This coordinate regulation of enzyme activity and the accessibility of platelets led to their use as a surrogate for enzyme activity in human population studies. Some studies have shown that SULT1A1 platelet enzymatic activity varies by gender and by season (Marazziti et al, 1995(Marazziti et al, , 1998Nowell et al, 2000). Interestingly, megakaryocytes, parental cells of the platelet, express both estrogen and androgen receptors, leading to the speculation that steroids could modulate the expression of enzymes found in the platelet (Tarantino et al, 1994;Khetawat et al, 2000).…”
Section: Sult1a1mentioning
confidence: 99%
“…A study by Brittelli et al (1999) showed that SULT1A1 activity was significantly different between Spaniards and Finns, and in the case of the Finnish population, phenotype also varied by gender. Platelet SULT1A1 phenotype also tends to be higher in African Americans compared to Caucasians (Anderson et al, 1988;Nowell et al, 2000).…”
Section: Sult1a1mentioning
confidence: 99%